The Number of Adverse Childhood Experiences Is Associated with Emotional and Behavioral Problems among Adolescents - Lackova Rebicova, Miriama; Dankulincova Veselska, Zuzana; Husarova, Daniela; Madarasova Geckova, Andrea; van Dijk, Jitse P; Reijneveld, Sijmen A (International journal of environmental research and public health, 2019)
This study aims to examine the association of adverse childhood experiences (ACE) with emotional and behavioral problems (EBP) among adolescents and the degree to which this association is stronger for more ACE. In addition, we assessed whether socioeconomic position (SEP) modifies the association of ACE with EBP. We obtained data from 341 adolescents aged 10-16 (mean age = 13.14 years; 44.0% boys), the baseline of a cohort study. We measured EBP with the strengths and difficulties questionnaire and socioeconomic position (SEP) with self-reported financial status. We used generalized linear models to analyze the association between ACE (0 vs. 1-2 vs. 3 and more) and EBP, and the modifying effect of SEP. Adolescents with 1-2 ACE (regression coefficient: 0.19; 95%-confidence interval (CI): 0.06-0.32) and with 3 ACE and over (0.35; 0.17-0.54) reported more overall problems compared with adolescents without ACE. Moreover, adolescents with 1-2 ACE (0.16; -0.01-0.32, and 0.16; 0.03-0.29) and with 3 and over ACE (0.33; 0.10-0.56, and 0.28; 0.09-0.47) reported more emotional problems and behavioral problems, respectively. The interactions of SEP with ACE were not significant. ACE are related to EBP among adolescents, with a clear dose-response association, and this association similarly holds for all SEP categories.
Keywords: Adolescent Behavior; emotional problems; Male; kohortové studie; emoce; zpráva o sobě; adverse childhood experiences; Cohort Studies; Mental Disorders; Adolescent; Problem Behavior; Child; Emotions; dítě; mužské pohlaví; nepříznivé zkušenosti z dětství; behavioral problems; duševní poruchy; mladiství; lidé; ženské pohlaví; Humans; adolescence; Adverse Childhood Experiences; Self Report; problémové chování; Female; chování mladistvých